Cryoballoon vs. radiofrequency ablation for atrial fibrillation: a study of outcome and safety based on the ESC-EHRA atrial fibrillation ablation long-term registry and the Swedish catheter ablation registry. Issue 4 (29th October 2018) - Mörtsell, David; Arbelo, Elena; Dagres, Nikolaos; Brugada, Josep; Laroche, Cécile; Trines, Serge A; Malmborg, Helena; Höglund, Niklas; Tavazzi, Luigi; Pokushalov, Evgeny; Stabile, Giuseppe; Blomström-Lundqvist, Carina; et al.
Abstract: Aims: Pulmonary vein isolation (PVI), the standard for atrial fibrillation (AF) ablation, is most commonly applied with radiofrequency (RF) energy, although cryoballoon technology (CRYO) has gained widespread use. The aim was to compare the second-generation cryoballoon and the irrigated RF energy regarding outcomes and safety. Methods and results: Of 4657 patients undergoing their first AF ablation, 982 with CRYO and 3675 with RF energy were included from the Swedish catheter ablation registry and the Atrial Fibrillation Ablation Long-Term registry of the European Heart Rhythm Association of the European Society of Cardiology. The primary endpoint was repeat AF ablation. The major secondary endpoints included procedural duration, tachyarrhythmia recurrence, and complication rate. The re-ablation rate after 12 months was significantly lower in the CRYO vs. the RF group, 7.8% vs. 11%, P = 0.005, while freedom from arrhythmia recurrence (30 s duration) did not differ between the groups, 70.2 % vs. 68.2%, P = 0.44. The result was not influenced by AF type and lesion sets applied. In the Cox regression analysis, paroxysmal AF had significantly lower risk for re-ablation with CRYO, hazard ratio 0.56 ( P = 0.041). Procedural duration was significantly shorter with CRYO than RF, (mean ± SD) 133.6 ± 45.2 min vs. 174.6 ± 58.2 min, P < 0.001. Complication rates were similar; 53/982 (5.4%) vs. 191/3675 (5.2%), CRYO vs. RF, P = 0.806. Conclusion: The lower re-ablation rates and shorter procedure times observed with the cryoballoon as compared to RF ablation may have important clinical implications when choosing AF ablation technique despite recognized limitations with registries.